Integrative Education in Amin Abdullah's Philosophy: A Contemporary Reinterpretation for Islamic Pedagogy - Khasanah, Mita Nur; Yusgiantara, Akbar; Asy Syakur, Albert Taqy; Baidi (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2025)
This research rigorously reexamines Amin Abdullah's integrative-interconnected epistemology to provide a pedagogical framework suitable for modern Islamic education. Although Abdullah's framework has profoundly impacted the reformation of Islamic epistemology in Indonesian higher education, its practical application at the pedagogical level is still lacking development. This research utilizes a qualitative library research approach and theme analysis to integrate primary and secondary materials systematically, therefore connecting epistemological Theory with classroom practice. Research indicates that although epistemological integration has influenced institutional curriculum, it has not been implemented in instructional design, learning methodologies, and evaluation models in Islamic Education (Pendidikan Agama Islam/PAI). This research presents a context-sensitive educational paradigm grounded on Abdullah's transdisciplinary, dialogical, and ethical principles. The paradigm prioritizes thematic-integrative learning, critical analysis of religious texts, and the cultivation of social and moral literacy within the classroom environment. This work enhances the debate on Islamic educational reform by converting epistemological notions into instructional practice, contributing both theoretically and practically. The suggested method not only improves educational significance but also establishes Islamic education as a transformational entity by 21st-century requirements.